Interferensi Fonologi Wasedaboys terhadap Nama-Nama Daerah Indonesia pada Vlog Nihongo Mantappu - Rahardjo, Hardianto (KIRYOKU, 2024)
Interference is a mistake that is generally made by second language learners because of the influence of their first language skills.  Meanwhile, phonological interference is an error that occurs at the sound level due to changes in phonemes that are influenced by knowledge of the sound system in the first language.  This proposal discusses the mistakes of second language learners (in this case, Wasedaboys) in understanding sound changes that occur in the language being studied (Indonesian).  This study aims to describe the forms and factors that cause phonological interference by Wasedaboys in writing the names of regions in Indonesia in the vlog "Nihonggo Mantappu" entitled "quiz spelling Indonesian regional names w/ wasedaboys!  How ridiculous!  The method used in this research is descriptive qualitative method with theory referring to Weinrich's (1953) interference theory.  The data collection method used is the listening method with the proficient free engagement technique.  Based on the data that has been obtained, the forms of phonological interference found are classified into forms of interference with phoneme changes, interference with the addition of phonemes and forms of interference with phoneme deletion in which the forms of interference mentioned above occur at the level of vowel and consonant phonemes.  The factors that cause phonological interference are (1) the bilingualism of the speech participants, totaling 3 data, (2) differences in vowel sounds and writing methods, totaling 11 data, (3) carrying over their mother tongue, totaling 3 data.Keywords: interference, phonology, vlog, Wasedaboys, Japan